Pengaruh Konsumsi Kurma (Phoenix Dactylifera) terhadap Kadar Hemoglobin pada Siswi Kelas XI di SMA 1 Grogol Kabupaten Kediri - Dily Ekasari; Eko Winarti; Sutrisni Sutrisni (Dian Nuswantoro Semarang, 2017)
Date palm (Phoenix dactylifera) is fruit that have many benefits for the human body because it contains iron, kalium and riboflavin which is essential to prevent anemia. According to the Health Department (2011), female adolescent that suffer anemia was 26.50%. One of the laboratory sign of anemia is low of hemoglobin levels. This reaserch aims to find the effect of dates consumption against the hemoglobin levels of the XI class school girl in Grogol 1 Senior High School Kediri Regency, 2014. This study used pre-experimental design with one group pretest-posttest design method. The population was the XI grade female students in Grogol 1 Senior High School Kediri Regency, 2014. The sample of this study were 15 female students who did not menstruate, suffered middle anemia and low anemia taken using accidental sampling technique. The data collected by used the research check-list, measurement of hemoglobin levels before dates consume by using the Î²-hemoglobin hemoque and then measured againafter treatment. The data was analysed by using the paired sample T test and that processed with SPSS. The results showed after consuming dates, the hemoglobin levels increased average of 0.93 gr% (Ï = 0.000). The dates consumption had effect the hemoglobin levels of the XI female students in Grogol 1 Senior High School Kediri Regency.Keywords: dates, hemoglobin levels